Geometry and Measurement in Quran - Huda, Nuril (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
The Quran contains the basic principles of science and civilization. These sciences include natural science and mathematics. The study of mathematics covers algebra, statistics, logic, geometry, measurement, and others. This research aimed to examine the verses of the Quran, which contain geometry and measurement concepts. This research employed the descriptive-qualitative method with library research design. This research revealed that the Quran contains five concepts of geometry: three concepts of line and two concepts of angle. Meanwhile, the Quran also contains fourteen concepts of measurement: six units of time, five units of weight, two units of area, and two units of length or distance.